Introductory chemistry : concepts and critical thinking - Corwin, Charles H. (Boston : Prentice Hall, 2011)
To help students learn chemical skills and concepts more effectively, Introductory Chemistry: Concepts and Critical Thinking, Sixth Edition highlights the connection between key concepts and key problem-solving skills through critical thinking. Math and problem solving are covered early in the text; Corwin builds your problem-solving ability through innovative learning aids and technology formulated to meet your needs. This revision retains all the strengths of the previous editions, while adding emphasis on conceptual understanding and critical thinking.
Includes bibliographical references and index.
Keywords: Chemistry -- Textbooks